Once a Giant, (Almost) Always a Giant: Partial Tidal Disruption Events of Giant Stars - Núria Navarro Navarro; Tsvi Piran (The Astrophysical Journal)
Tidal disruption events (TDEs) of giant stars by supermassive black holes (SMBH) differ significantly from those of main-sequence ones. Most (all for SMBH of more than a few ×10 ^5 m _⊙ ) giant TDEs are partial: only a fraction of the envelope is torn apart. The dense stellar core and the rest of the envelope remain intact. In this work we explore, using the stellar evolution code MESA , the fate of the remnants. We find that after a short period, comparable to the thermal timescale, the remnant returns to a giant structure with a radius comparable to the progenitor giant one, a slightly larger luminosity (as compared with a regular giant with the same mass), and a comparable lifetime until it collapses to a white dwarf. If such a giant with a mass less than ≈0.9 m _⊙ is discovered, it can be identified as an outlier—a giant that is too light for the current age of the Universe. If the remnant orbit is not perturbed significantly during the encounter, the remnant will undergo successive partial tidal disruptions until its mass is 0.6–0.7 m _⊙ . We expect a few dozen to a few hundred such remnants in the Galactic nucleus.